2020
DOI: 10.1021/acscatal.0c03492
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Controlled Regioselective Carbonylation of Isobutylene Oxide to Pivalolactone

Abstract: Poly(pivalolactone) (PPVL) is a crystalline polyester with attractive physical and mechanical properties; however, prohibitively expensive syntheses of pivalolactone have thwarted efforts to produce PPVL on an industrial scale. Therefore, we developed a class of highly regioselective sandwich-type catalysts for the carbonylation of isobutylene oxide. These sterically encumbered complexes install carbon monoxide at the substituted epoxide carbon, generating a high level of contrasteric selectivity (up to >99:1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Recent efforts by Coates and co-workers have focused on developing a catalyst-controlled, contrasteric-selective carbonylation of isobutylene oxide for the production of pivalolactone and poly(pivalolactone). 32 Without a directing group or electronic control, this objective was particularly challenging due to the inherent, counterproductive steric substrate bias of 2,2-disubstituted epoxides. To reduce the quantity of steric product generated, the authors synthesized a ligand with additional bulk surrounding the epoxide binding pocket.…”
mentioning
confidence: 99%
“…Recent efforts by Coates and co-workers have focused on developing a catalyst-controlled, contrasteric-selective carbonylation of isobutylene oxide for the production of pivalolactone and poly(pivalolactone). 32 Without a directing group or electronic control, this objective was particularly challenging due to the inherent, counterproductive steric substrate bias of 2,2-disubstituted epoxides. To reduce the quantity of steric product generated, the authors synthesized a ligand with additional bulk surrounding the epoxide binding pocket.…”
mentioning
confidence: 99%
“…In 2020, Coates and co-workers developed a catalystcontrolled, contrasteric-selective carbonylation of isobutylene oxide to produce pivalolactone and poly(pivalolactone) (Figure 10b). 76 The catalyst 19 was envisioned with additional steric bulk at the epoxide binding site, which prevents the nucleophile from attacking the less sterically hindered position. Moreover, partial positive charge at the more congested site on the epoxide can be stabilized via noncovalent interaction (Figure 10c).…”
Section: Carbonylation Of Epoxidesmentioning
confidence: 99%
“…[34] Coates et al also reported the synthesis of 𝛽-lactones by epoxides and carbon monoxide under the catalysis of metal complexes. [35][36][37][38][39] This provided a way to synthesize monomers for this study. In the past decades, this method has been successfully applied to the alternating copolymerization of other lactone monomers, and the relationships between sequence structure and performance of copolyesters were also studied.…”
Section: Syndioselective Roap Of 𝜷-Lactonesmentioning
confidence: 99%